'Do What the Afro-Americans Are Doing': Black Power and the Start of the Northern Ireland Troubles. (July 2015) - Prince, Simon
This article challenges the local focus of much of the work on the Northern Ireland Troubles, by examining the importance of the impact that Black Power movements had on activists in the 1960s and 1970s. It is not, however, the story of the transnational diffusion of the ideas of a US movement to a nation-state on the periphery. Conceiving of the West in the 'cycle of protest years' as a networked space, this article argues that Northern Ireland during its Black Power moment was the unique and fleeting coming together of many different trajectories. The left-wing activists used Black Power to build transnational networks of revolt and to inspire local political struggles; the British authorities used the information that they collected from around the world on Black Power as a lens through which to view subversives and as a resource for making strategy. The start of the Troubles was interpreted by actors on both sides of the barricades as a forerunner of the class and race conflicts to come in the West, not as the latest small, local war in Britain's retreat from empire.